Semiotics and didacticsA dialogue by Algirdas Julien Greimas and Jacques Fontanille(Translation) (مجلة إحالات, 2026)
This is a translation of a dialogue that took place between two eminent semiotics, AlgirdasJulien Greimas and Jacques Fontanille, whose content is the relationship between semiotics and didactics, and the use of semiotic models in educational discourse, in order to control competence, while teaching literature, for example. It is a goal sought by all persuasive discourse, those which tend to have an educational vocation, analogous to political discourse and publicity discourse.